Detection of neotectonic deformations along the Rio do Peixe Valley, Western São Paulo State, Brazil, based on the distribution of late Quaternary allounits - Etchebehere, Mario Lincoln; Saad, Antonio Roberto; Fulfaro, Vicente José; Perinotto, José Alexandre J. (Revista Brasileira de Geomorfologia, 2005)
Terrace deposits (34 10 ka) were mapped in the Rio do Peixe valley and submitted to an allostratigraphic analysis. Three allomembers (viz. “A”, “B”, and “C” ) were established in the medium to lower river valley and other three allounits (allomembers “ L”, “M” and “N”) were defined in the upper valley. It is probable tha “B” and “M” allomembers represent the same stratigraphic level. The spatial distribution of these allomember shows the influence of the Recent base-level changes, due to neotectonics events. Longitudinal cross-section o the Rio do Peixe valley shows that it is possible to define some areas with differential tectonic movements, tha includes uplift blocks (prone to erosion and terrace deposit destruction), and other areas with relative subsidence, controlling both the Recent alluvial plains and the preservation of some ancient terrace deposits. This scenery is in accordance with regional tectonic studies.